THE INFLUENCE OF ORTHODONTIC TREATMENT ON PERIODONTITIS-SUSCEPTIBLE PATIENTS. A REVIEW - Ioana-Andreea Sioustis; Alexandra-Cornelia Teodorescu; Maria-Alexandra Martu; Diana-Cristala N; Ionut Luchian; Bogdan Vasiliu; Irina-Georgeta Sufaru; Liliana Pasarin; Ioana Rudnic; Silvia Teslaru; Sorina-Mihaela Solomon; Silvia Martu (Romanian Dental Association for Education, 2021)
The influence of orthodontic treatment on periodontitis-susceptible patients is a subject of interest. Dental malposition caused by periodontal disease are often observed in this type of patients. Also, these patients often are undergoing orthodontic treatment in order to restore the esthetics and functions of the dental and periodontal apparatus. Thus, it is important to question and verify in what conditions and parameters the orthodontic treatment improves the status of the periodontium. This review analyses several studies concerning this important topic and highlights the parameters that influence the outcome of orthodontic treatment.